2011
DOI: 10.1159/000331132
|View full text |Cite
|
Sign up to set email alerts
|

Significant Elevation of Survivin and Livin Expression in Human Colorectal Cancer: Inverse Correlation between Expression and Overall Survival

Abstract: Background: Survivin and livin are novel members of the inhibitor of apoptosis protein family, which have rarely been studied in human colorectal cancer (CRC). This study aims to examine their expression and association with clinicopathological factors and prognosis in CRC, and evaluate the possibility of their use as biomarkers for CRC. Patients and Methods: We investigated the expression of survivin and livin in 61 CRC samples using immunohistochemical staining (Envision) and correlated it with the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 25 publications
1
31
0
3
Order By: Relevance
“…It has been demonstrated to be expressed in transformed cells and multiple types of malignant tumor, including neuroblastoma (20) as well as carcinomas of the bladder (21,22), lung (23), nasopharynx (24), kidney (25), liver (26), colon/rectum (27), skin (28), bone (29) and stomach (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated to be expressed in transformed cells and multiple types of malignant tumor, including neuroblastoma (20) as well as carcinomas of the bladder (21,22), lung (23), nasopharynx (24), kidney (25), liver (26), colon/rectum (27), skin (28), bone (29) and stomach (30).…”
Section: Discussionmentioning
confidence: 99%
“…Livin, a novel member of the inhibitor of apoptosis (IAP) protein family, is not detected in the majority of normal tissues, however, is highly expressed in various types of human malignancy (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Increased activity of this protein may be used as a reliable prognostic factor for initial and late resistance to chemotherapeutic drugs in certain types of human tumor (31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…Hernandez et al (17) confirmed the presence of this protein in 93% of patients with colon cancer, while Xi et al (18) observed its expression in 60.7% of CRC patients. Survivin has different functions depending on its location.…”
Section: Survivin (Pg/ml) -------------------------------------------mentioning
confidence: 96%
“…Previous studies have demonstrated that the expression level of BIRC7 is significantly up-regulated in colorectal cancer, and negative in normal colonic mucosa, and univariate survival analysis have shown that the expression level of BIRC7 is negatively correlated with survival time [35].The positive expression rate of BIRC7 in patients with advanced neuroblastoma is significantly higher than that in patients at early or intermediate stage [36]. In this studies, we observed that overexpressions of BIRC7, in both SC/ASC and AC, were significantly associated with large tumor size, high TNM stage, lymph node metastasis, invasion and poor survival.These results might suggest that BIRC7 is a tumor maker for reflecting the carcinogenesis, progression , biological behaviors and prognosis in both SC/ASC and AC of gallbladder.…”
Section: Discussionmentioning
confidence: 99%